2009 14th IEEE European Test Symposium 2009
DOI: 10.1109/ets.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

Categorizing and Analysis of Activated Faults in the FlexRay Communication Controller Registers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…This paper extends the work presented in [18]. The extension includes three parts: 1) A new error type called Invalid frame error is added in the study; 2) Fault effects are classified individually in the target node and in the neighbor node; and 3) Error propagation rates from the target node to the neighbor node are investigated.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…This paper extends the work presented in [18]. The extension includes three parts: 1) A new error type called Invalid frame error is added in the study; 2) Fault effects are classified individually in the target node and in the neighbor node; and 3) Error propagation rates from the target node to the neighbor node are investigated.…”
mentioning
confidence: 85%
“…More detailed reinvestigations of the fault injection results showed that due to an injected fault, a received frame which has none of mentioned error types in [18] may be dropped by the communication controller. Hence, the [5] were reviewed again, carefully.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations